THE DESIRE FOR SOCIAL DEVELOPMENT AND THE EMERGENCE OF IDEAS OF MODERNISM ON THE TERRITORY OF TURKESTAN (Web of Teachers: Inderscience Research, 2024)
This article describes the emergence of freedom-minded Jadids educators as a result of the policy of violence in the social, economic and political spheres after the occupation of Turkestan by Tsarist Russia, as well as the emergence of protests from various strata of peoples.